Availability and confidentiality in storage clouds - André, Fernando Martins (2010)
Cloud Computing and Cloud Storage in particular are rapidly transforming the nature of how business use information technology based on a software-as-a-service model. The main aspect of this paradigm changing is the fact that data is leaving organizations data centers and is being outsourced to cloud providers infra- structures. For Cloud Storage in concrete, there are many appealing advantages on using this new approach such as the opportunity to use a completely ﬂexible web-scale storage service, available from any point in the world with an Internet connection. However, from a security perspective, this advance also poses new and critical security threats. Issues like data loss or leakage, availability, conﬁdentiality, integrity and malicious insiders are amongst the most referenced concerns when deciding to move data to the cloud. The DepSky system already addresses some of these concerns. Therefore the aim of this work is divided in two main phases. First the DepSky system was object of improvement, by adding a new mechanism called Erasure Codes in the form of a library, and only after an analysis of some of the available Erasure Codes libraries in the Internet. Secondly, the availability of 4 (four) commercial cloud storage providers was studied using the logger application of DepSky. To achieve a realistic scenario, several loggers were deployed dispersed around the world in different geographical regions. Afterwards, a careful analysis of the resultant logs was made in order to assess and correlate several aspects such as latency (perceived availability), cost and differences in geographical regions. Therefore, this analysis and its results are the major contribution of this work